Relationship of Spontaneous Retinal Vein Pulsation with Ocular Circulatory Cycle - Kim, Mijin (Public Library of Science, 2014)
PURPOSE: To determine the timing of spontaneous venous pulsation (SVP) relative to the ocular circulatory cycle by using the movie tool of confocal scanning laser ophthalmoloscope. METHODS: A video recording of the fundus was obtained using a confocal scanning laser ophthalmoscope (Spectralis HRA, Heidelberg Engineering, Heidelberg, Germany) at 8 frames/s in 47 eyes (15 glaucoma patients and 32 glaucoma suspects) with visible pulsation of both the central retinal artery (CRA) and vein (CRV). The timing of the maximum and minimum diameters of the CRA (CRA(max) and CRA(min), respectively) and CRV (CRV(max) and CRV(min), respectively) was identified during four pulse cycles. The interval between CRV(min) and CRA(min), and between CRV(max) and CRA(max) was expressed as the number of frames and as a percentage of the ocular circulatory cycle. RESULTS: The ocular circulatory cycle (from one CRA(max) to the next) lasted 7.7±1.0 frames (958.8±127.2 ms, mean±SD), with a mean pulse rate of 62.6 beats/min. The diameter of the CRA was increased for 2.4±0.5 frames (301.9±58.8 ms) and decreased for 5.3±0.9 frames (656.9±113.5 ms). CRV(max) occurred 1.0±0.2 frames after CRA(max) (equivalent to 13.0% of the ocular circulatory cycle), while CRV(min) occurred 1.1±0.4 frames after CRA(min) (equivalent to 14.6% of the ocular circulatory cycle). CONCLUSIONS: During SVP, the diameter of the CRV began to decrease at early diastole, and the reduction persisted until early systole. This finding supports that CRV collapse occurs during ocular diastole.